STRUKTUR DAN KOMPOSISI HUTAN MANGROVE LIKUPANG KABUPATEN MINAHASA UTARA PROVINSI SULAWESI UTARA - Felly E. Sengkey; Martina A. Langi; Johny S. Tasirin (COCOS, 2015)
ABSTRACT The most of natural Indonesia area is dominated by water teritorial which consist of thousands of island with souronded by mangrove. Functions and benefits of mangroves have been widely known, both as a place of spawning fish in the waters, land protector of abrasion due to waves, winds from the mainland protector, filter sea water intrusion inland and content of heavy metals that are harmful to life, a haven of migratory birds, and as wildlife habitat and other direct benefits for humans. The purpose of this research is aimed to analyze the structure and composition of mangrove vegetation found in the District Likupang, North Minahasa Regency, North Sulawesi. This research was conducted using the transect method and terraced path, by surveying observations and direct measurements in the field and then analyzed descriptively. The collected data are presented in tables and graphs. The results showed that the structure of mangrove forests Likupang for seedling phase dominated by Sonneratia sp, for the sapling phase is dominated by Avicennia alba and to phase dominated by Sonneratia sp while for there phase dominated by Sonneratia sp and mangrove forest composition Likupang are dominated by Sonneratia sp followed by the type Rhizopora sp., and Bruguera sp. Â Key words: Forest Mangrove, Mangrove types, structure and composition of the Mangrove Â